Proposed object-based e-learning framework embracing cloud computing - Wang, Lillian Yee Kiaw; Lau, Siong Hoe; Lew, Sook Ling; Leow, Meng Chew (2015)
E-learning is continually evolved in the adaptation of emerging technologies and pedagogies, so does the development of learning objects. Object-based learning approach has been widely adopted in e-learning.The principle concern in the conventional e-learning models is the inflexibility of the e-learning content to assist the use and management of the learning sources which are highly distributed.Rigidity of e-learning content limits its reusability and shareability.Possessing the ability to deliver strong computing power and secure data storage as services, Cloud computing is a promising computing model to promote innovative changes and add notable values to e-learning landscape.The flexibility and on-demand access to a centralized shared pool of computing resources provided by Cloud computing enables high re-usability and share-ability, hence overcomes the principle concern in e-learning due to the rigidity of e-learning content.This paper describes the design of an object-based e-learning framework embracing Cloud computing.The proposed object-based e learning framework can be used to form a new education domain that shares the Cloud characteristics of elasticity, flexibility, efficiency and reliability.Principal to the framework design is the development of Cloud-based e-learning objects where learners have the flexibility to access, personalize and deploy them in e-learning environment.Cloud-based e-learning objects are highly adaptable, reusable and easy changeable, hence allowing them to be used dynamically with greater customizability and flexibility in e-learning.Adapting Cloud computing into object-based e-learning is believed to be able to create a breakthrough in future dynamic -e-learning development.